Bangladesh : Staff Report for the 2003 Article IV Consultation and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2003)
Bangladesh achieved steady gross domestic product growth with manageable inflation, and improved social indicators, owing to prudent macroeconomic management and a renewal of structural reform. The proposed Poverty Reduction and Growth Facility-supported program builds on this record of policy implementation. Fiscal reform should be centered on a sustained revenue effort and investments in infrastructure and human capital. The government has been commended for the flexible management of the exchange rate. Executive Directors consider the proposed policy program to be comprehensive and realistic for achieving the objectives.